Agronomic potential value of household urban solid wastes by composting and composts quality assessment - KKA Alate (International Journal of Agricultural Research, Innovation and Technology, 2019)
Using composting technology, the biodegradable fraction of solid wastes collected from Agbalepedogan district in Lomé (Togo) was transformed into composts with no phytotoxicity suitable for use in agriculture. The household urban solid wastes were mixed with poultry manure and Mucuna pruriens leaves in appropriate percentages and transformed into composts. The composting process was monitored by temperature, pH and C/N ratio controlling. The composts quality was appreciated by phytotoxicity test, particle size distribution, contents of nitrogen, phosphorus, potassium, organic matter and trace elements. The results showed that composts particle size distribution presented four fractions (>10 mm, 5-10 mm, 2-5 mm and ≤2 mm) whose average percentages are respectively 9.04±0.2%; 10.71±0.2%; 12.68±0.4% and 67.53±0.6%, respectively. Composts produced contained 1.02±0.1% - 2.72±0.2% of nitrogen, 1.35±0.3% - 2.70±0.4% of phosphorus, 1.31±0.2% - 1.72±0.3% of potassium and 23.50±0.4% - 37.75±0.5% of organic matter. The pH in final composts were between 8.50±0.2 and 9.00±0.3 while C/N ratio varying from 8.06±0.2 to 13.13±0.2. The concentrations of some heavy metals in final products were 79.8±1.7 - 140.2±1.6 mg/kg.dm of zinc, 27.1±1.01 - 76.6±1.03 mg/kg.dm of copper, 2.07±0.33 - 9.19±0.22 mg/kg.dm of lead, 4.13±0.16 - 11.05±0.36 mg/kg.dm of nickel and 0.79±0.02 - 2.15±0.03 mg/kg.dm of cadmium. These concentrations were lower than the limited value for heavy metals prescribed by French and US EPA regulation for organic and organic-mineral fertilizers.